Emotion Regulation Focused Family Therapy With Contemporary Families Affected by Information and Communication Technologies - Duriez, Nathalie (Frontiers in Sociology, 2021)
In the contemporary world, new Information and Communication Technologies have revolutionized family relationships and organization. Mobile phones, tablets and computers are entrenched in everyday family life. Therefore, families face new challenges with problematic internet use, blurring boundaries between the outside world and the domestic sphere. Sometimes these changes in living together lead to suffering. How do therapists respond to these new challenges faced by contemporary families? Considering the emotion regulation strategies underlying the problematic use of technology, we develop an Emotion Regulation Focused Family Therapy. Within the Change Process Research paradigm, which aims to explain how psychotherapy produces change, we examine this innovative therapeutic approach in an exploratory process in order to refine our own practice. We conducted a grounded theory qualitative research for five families in family therapy under natural clinical conditions to identify the therapist’s interventions and the family configurations. The core theme was therapist interventions. The results identified twelve subcategories under this category. We built an emotion regulation focused model with twelve steps from these subcategories. Each of the interventions is illustrated with some excerpts from the sessions. Clinical considerations, methodological issues limiting the current body of work, and recommendations for future research are discussed.